Ditching Dualisms: Education Professionals View the Future of Technology and Disabilities - Lise Bird Claiborne (Disability Studies Quarterly, 2005)
Small groups of educational psychologists, disability educators, and teachers with special education training were interviewed about the likely impact of new technologies for bodily enhancement on their future practice. New theories of embodiment (e.g. Deleuze, Grosz) consider human selves beyond bounded, individual containers. Such ideas also appear in popular media, because films often challenge conventional notions of character and time. To frame the research discussions, three short documentary films were created to present issues that raised questions about dualisms such as nature/nurture and natural/technological. Professionals reflected critically on nature and saw many parallels between different kinds of enhancement, whether mechanistic, chemical, or genetic. Questioning dualistic ideas about nature was also seen as having the potential to alter contemporary views of prosthetics, expanding possibilities for what it means to be human.
Keywords: new technology for bodily enhancement; theories of embodiment; nature/nurture; special education instructors